The Mountain, the Miner, and the Lord and Other Tales from a Country Law Office - Caudill, Harry M., 1922-1990 (Book collections on Project MUSE., 1980)
This book of stories celebrates people who have a magnetism, a tenacity, a personal vision, an independence, and a self-sufficiency that elude most of us today.